Macrobenthic fauna associated with the invasive alien species Brachidontes pharaonis (Mollusca: Bivalvia) in the Levantine Sea (Turkey). (27th February 2017) - Çinar, Melih Ertan; Bakir, Kerem; Öztürk, Bilal; Katağan, Tuncer; Doğan, Alper; Açik, Sermin; Kurt-Sahin, Güley; Özcan, Tahir; Dağli, Ertan; Bitlis-Bakir, Banu; Koçak, Ferah; Kirkim, Fevzi
Abstract : The invasive alien mytilid species, Brachidontes pharaonis, forms a biogenic habitat in the mediolittoral and upper-infralittoral zones of the Levantine Sea, hosting a number of alien and native species. Examinations of samples taken from dense, continuous mussel beds at seven stations along the coast of northern Levantine Sea yielded 187 macro-benthic invertebrate species belonging to 11 taxonomic groups. Polychaeta accounted for 46% and 37% of the total number of species and individuals, respectively. The top three dominant species in the mussel beds were Stenothoe gallensis, Spirobranchus kraussi and Mytilaster minimus . The species with the highest frequency values on the mussel beds were Pseudonereis anomala, Phascolosoma stephensoni and Elasmopus pocillimanus . The highest density and biomass of the associated fauna were estimated as 42, 550 ind m −2 and 1503 wwt g m −2, respectively. The species number in samples varied between 14 and 47 species. The environmental variables best explaining variations in zoobenthic community structures were salinity, dissolved oxygen and total inorganic nitrogen in the water column. The biotic indices, TUBI and ALEX, classified the ecological status of one or two stations as moderate or poor, based on the relative abundances of ecological and zoogeographic groups, respectively. A total of 21 alien species were found to be associated with the mussel bed, of which Syllis ergeni is being newly considered as a new established alien species for the Mediterranean Sea. The maximum density of associated alien species was calculated as 30, 300 ind m −2 . The alien species assemblages were greatly affected by salinity and total inorganic nitrogen.